Body weight and return to work among survivors of early-stage breast cancer. Issue 6 (10th November 2020) - Di Meglio, Antonio; Menvielle, Gwenn; Dumas, Agnes; Gbenou, Arnauld; Pinto, Sandrine; Bovagnet, Thomas; Martin, Elise; Ferreira, Arlindo R; Vanlemmens, Laurence; Arsene, Olivier; Ibrahim, Mahmoud; Wassermann, Johanna; et al.
Abstract : Background: Many breast cancer (BC) survivors are employed at diagnosis and are expected to return to work after treatment. Among them, around 50% are overweight or obese. There are limited data about the impact of body weight on their ability to return to work. Methods: We used data from CANcer TOxicity (NCT01993498 ), a prospective, multicentre cohort of women with stage I–III BC. Professionally active women who were ≥5 years younger than retirement age were identified. Multivariable logistic regression models examined associations of body mass index (BMI) at diagnosis and subsequent weight changes with non-return to work 2 years after diagnosis, adjusting for psychosocial, treatment and behavioural characteristics. Results: Among 1869 women, 689 were overweight or obese. Overall, 398 patients (21.3%) had not returned to work 2 years after diagnosis. Non-return to work was more likely for overweight or obese than underweight or normal weight patients (adjusted OR (aOR) 1.32; 95% CI, 1.01 to 1.75; p=0.045). Weight loss (≥5%) was observed in 15.7% overweight or obese and 8.7% underweight or normal weight patients and was associated with significant increases in physical activity only among overweight or obese patients (mean change, +4.7 metabolic-equivalent-of-task-hour/week; 95% CI +1.9 to +7.5). Overweight or obese patients who lost weight were more likely to return to work compared with those who did not lose weight (aOR of non-return-to-work, 0.48; 95% CI 0.24 to 0.97, p=0.0418), whereas weight loss was associated with increased odds of non-return to work among underweight or normal weight women (aOR 2.07; 95% CI 1.20 to 3.56, p=0.0086) (pinteraction BMI×weight changes=0.0002). The continuous trend of weight gain on non-return to work was significant for overweight or obese patients (aOR for one-percent-unit difference, 1.03; 95% CI 1.01 to 1.06, p=0.030). Conclusions: Excess weight may be a barrier to return to work. Among overweight or obese BC survivors, weight loss was associated with higher rates of return to work, whereas further weight gain was associated with lower likelihood of return to work. Employment outcomes should be evaluated in randomised studies of weight management.